LISTEN ENGLISH FULL AUDIO as a SUPPORTING MEDIA in IMPROVING STUDENTS’ LISTENING SKILL - Palangngan Tono Sukmawati; Mulyaningsih Eka (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2018)
Listen English Full Audio is a smartphone application that can be downloaded freely from a smartphone. In this modern Era smartphone is not a rare thing anymore because most of the students even all the students have their own gadget or smartphone. So, the students can use this application wherever and whenever they want. The aims of this research are to find out whether the use of Listen English Full Audio Application can help the students to improve their listening skill. Furthermore, it also focuses in analyzing the students’ perception toward the application. The method used in this research is Quan-Qual method with a type of quasi experimental design namely regression discontinuity design. The population is the first semester of STKIP Muhammadiyah Palopo students academic year 2017/2018. The total number of population was 240 students. Related to the sampling technique, this research uses the combination of random sampling and non random sampling technique. Random sampling is used to decide the sample of the quantitative analysis and non random sampling to decide the qualitative analysis. The data are collected by test which is analyze by using SPSS 20 program and interview which is analyze by using open coding. The result showed that Listen English Full Audio is affective in improving the students’ listening skill. Furthermore, all students agree that English Listen English Full Audio is a good supporting media.